Analisis Teoritis Penerapan Communicative Language Teaching (CLT) dalam Pembelajaran Bahasa Arab di Perguruan Tinggi Islam - Zayid Abdul Jabar Asshidiqie; Dadan Mardani; Iis Susiawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to provide a theoretical analysis of the implementation of the Communicative Language Teaching (CLT) method in Arabic language instruction at Islamic Higher Education institutions. The research is grounded in the reality that Arabic teaching in Indonesia remains dominated by traditional approaches focused on grammar and translation, while students’ communicative competence remains relatively low. Employing a qualitative approach through library research, the study collected data from books, journal articles, theses, and other relevant documents, which were critically analyzed and synthesized. The findings reveal that CLT is theoretically grounded in the view of language as communication and in the framework of communicative competence. The advantages of CLT include increasing learning motivation, language fluency, active participation, and the integration of the four language skills. However, its application faces several challenges, particularly at the institutional level, such as limited lecturer competence, large class sizes, inadequate teaching materials, passive learning culture, and insufficient infrastructure. A critical analysis affirms that CLT is highly relevant in addressing the challenges of Arabic language teaching in the modern era, especially in the context of Islamic Higher Education. This research is expected to serve as a conceptual foundation for developing more communicative, adaptive, and contextual Arabic teaching strategies. Keywords: Communicative Method, Arabic Language Teaching, Islamic Higher Education, Communicative Competence.